2015
DOI: 10.1088/0957-4484/26/16/164001
|View full text |Cite
|
Sign up to set email alerts
|

In-situ atomic layer deposition of tri-methylaluminum and water on pristine single-crystal (In)GaAs surfaces: electronic and electric structures

Abstract: The electronic structure of single-crystal (In)GaAs deposited with tri-methylaluminum (TMA) and water via atomic layer deposition (ALD) is presented with high-resolution synchrotron radiation core-level photoemission and capacitance-voltage (CV) characteristics. The interaction of the precursor atoms with (In)GaAs is confined at the topmost surface layer. The Ga-vacant site on the GaAs(111)A-2 × 2 surface is filled with Al, thereby effectively passivating the As dangling bonds. The As-As dimers on the GaAs(001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Also, no native oxides were detected, as examined using in-situ XPS and synchrotron radiation photoemission under the same transfer procedure [46]. The freshly MBE grown GaAs(001)-4 × 6 and GaAs(111)A-2 × 2 samples were in-situ transferred to the ALD reactor under UHV.…”
Section: Methodsmentioning
confidence: 99%
“…Also, no native oxides were detected, as examined using in-situ XPS and synchrotron radiation photoemission under the same transfer procedure [46]. The freshly MBE grown GaAs(001)-4 × 6 and GaAs(111)A-2 × 2 samples were in-situ transferred to the ALD reactor under UHV.…”
Section: Methodsmentioning
confidence: 99%
“…O 2 is introduced into the MBE chamber to compensate for the loss of oxygen from bombarding the oxide target upon the deposition of a high-κ dielectric oxide onto a Ge(001) wafer,. The partial pressure of O 2 is unreactive to the (In)GaAs substrates [35], but it is not entirely unaffected at the Ge substrate; the ALD is operating at a high pressure and it generates similar concerns for the oxygen residual. The established records of initial O 2 adsorption on Ge(001) have made their comments based on the very first work by Fukuda and Ogina two decades ago, who suggested that one of the dissociated O atoms of O 2 sits at the bridge site and the other sits at a backbond of the Ge-Ge dimer [34,36].…”
Section: Introductionmentioning
confidence: 99%
“…Upon deposition of high-κ dielectric oxides onto a Ge(001) wafer, O 2 is introduced into the molecular beam evaporation chamber in order to compensate for the loss of oxygen from bombarding the oxide target. The partial pressure of O 2 is immune to the (In)GaAs substrates, 14) but not entirely unaffected at the Ge substrate; atomic layer deposition (ALD) operating at a high pressure generates similar concerns for the oxygen residual. Established records of the initial O 2 adsorption on Ge(001) have made their comments based on the very first work by Fukuda and Ogina (FO) two decades ago, who suggested that one of the dissociated O atoms of O 2 sits at the bridge site and the other at a backbond of the Ge-Ge dimer.…”
mentioning
confidence: 99%